Empirically Derived Dietary Patterns in Association with Asthma Symptoms in Children and Adolescents: A Cross-Sectional Study - Samaneh Pishdad; Bahareh Sasanfar; Zahra Nafei; Mehran Karimi; Nasrin Behniafard; Amin Salehi Abarguoei (Journal of Nutrition and Food Security)
Limited data exists regarding the association between dietary patterns and asthma. This study aims to determine the relationship between empirically derived dietary patterns and the likelihood of asthma among a large population of children and adolescents living in central Iran. Methods: A total of 7667 of male and female students aged 6-14 from 48 public and private schools in YAZD urban areas entered the current cross-sectional study. Data on dietary intakes, as well as asthma symptoms and other possible confounders, were collected using a self-administered questionnaire filled by parents. Factor analysis was applied to find major dietary patterns. Multivariate logistic regression was performed to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for asthma development across quintiles of dietary patterns. Results: Two main dietary patterns were established. A “traditional diet” was determined by meat, fish, fruits, cooked vegetable, raw vegetable, legumes, cereals, bread, macaroni, rice, margarine, butter, olive oil, milk, yogurt, egg, nuts, potato, and a “western-like diet” was characterized by high intakes of simple sugars, fast food(hamburger), fast food (pizza), soft drinks, jelly, chocolate and biscuits of cocoa, ice cream, and sauce. After adjusting for potential confounders, individuals in the top quintile of traditional diet were 0.31 times less likely to have asthma than those in the lowest quintile (OR=0.69; 95% CI: 0.47-1.00). Moreover, individuals in the top quintile of traditional diet were 0.43 times less likely to have wheezing compared with those in the lowest quintile (OR=0.57, 95% CI: 0.46-0.70). However, individuals in the top quintile of the western diet were 0.35 times more likely to have wheezing than those in the lowest quintile (OR=1.35, 95% CI: 1.10-1.66). Conclusions: According to the results, a traditional diet might be associated with lower odds of asthma; however, a western-like diet might be adversely associated with asthma symptoms.